Collision Characteristics for Predicting Particle Attrition and Pipe Wear in Conveying Systems. Issue 8 (15th May 2018) - Uzi, Avi; Levy, Avi
Abstract: Pipe wear and particle attrition are common and undesired effects when conveying particles in pipelines. An approach for predicting these effects to spare considerable efforts spent in trial and error to achieve the optimum operating conditions is reported. The model is composed of a one‐dimensional flow model that calculates the two‐phase flow dynamics, a one‐dimensional breakage algorithm (ODBA) to compute attrition of the particles, and a one‐dimensional erosion model (ODEM) to compute the erosion rate. The ODBA and ODEM exploit machine functions derived from simulations that define collision characteristics. Several collision characteristics were successfully generated universally; therefore, allowing the attrition and erosion models to stand alone in the examined ranges. Abstract : Easy to implement, fast, and precise erosion and breakage models are essential for engineers to predict these effects in conveying systems. A major challenge is to evaluate the collision characteristics in terms of the flow conditions. These functions are produced by correlating them to governing parameters under different operating conditions to aid the prediction of attrition or erosion.